Revitalization: A Case Study of Likoni’s Urban Landscape - Jesse Murima Ayubu; Draughting Jorum Ayub (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The idea of having an area undergo revitalization carries with it some hope that a newness of some sort would possibly emerge if at all the end goal is attained. Observations around the world have been made on the impact that comes along with revitalization thus in a bid to not only partake in developing selected areas, policy makers also work tirelessly to bring the experience of such achievements to the locals hence sustaining the sensitivity of the flagship projects. Likoni, located in the southern region of Mombasa County, is one of the vibrant towns along the endowed Kenyan coast region. Recently, it has undergone a series of urbanization protocols although much can still be done to raise her status as a proper hub of urbanization. Being another town in a ‘global south’ region, it faces numerous challenges both internally and externally hence a limiting factor to its development.